Pengembangan E-modul berbasis Moodle dalam Pembelajaran IPA untuk Meningkatkan Keterampilan Argumentasi Ilmiah Siswa - Alfain Wahid Yanuarizal; Supeno Supeno; Rusdianto Rusdianto (Universitas Muhammadiyah Mataram, 2025)
Abstract: Scientific argumentation skills were a process in which two or more people built and criticized several arguments. Based on the results of observed at SMP Negeri 2 Kalipuro, students' scientific argumentation skills were very lacking. One learning strategy that can overcome the challenged of lacking scientific argumentation skills was Moodle-based e-modules. The purposed of this study was to test the validity, practicality and effectiveness of Moodle-based e-modules in science learning to improve students' scientific argumentation skills. This study was a development research using the ADDIE development model with the aim of producing teaching materials in the form of Moodle-based e-modules. Data collection for this study came from questionnaires, observations, and tests. The subjects of this study were class VII F students at SMP Negeri 2 Kalipuro. The results of the validity analysis obtained a percentage of 96.66%, the practicality analysis obtained a percentage of 94%, and the effectiveness analysis obtained an N-gain value of 0.69 which was included in the moderate category and also the percentage of student responses was 83.7%. From these results, it can be concluded that Moodle-based e-modules in science learning can be said to be valid, practical and effective in improving students' scientific argumentation skills.Abstrak: Abstrak: Keterampilan argumentasi ilmiah merupakan suatu proses dimana dua orang atau lebih membangun dan mengkritisi beberapa argumen. Berdasarkan hasil observasi di SMP Negeri 2 Kalipuro, keterampilan argumentasi ilmiah siswa masih sangat kurang. Salah satu strategi pembelajaran yang dapat mengatasi kendala kurangnya keterampilan argumentasi ilmiah adalah e-modul berbasis moodle. Tujuan penelitian ini adalah untuk menguji validitas, praktikalitas dan efektivitas e-modul berbasis dalam pembelajaran IPA untuk meningkatkan keterampilan argumentasi ilmiah siswa. Penelitian ini merupakan penelitian pengembangan dengan menggunakan model pengembangan ADDIE dengan tujuan menghasilkan bahan ajar berupa e-modul berbasis Moodle. Pengumpulan data penelitian ini menggunakan angket, observasi dan tes. Subjek penelitian ini adalah siswa kelas VII F SMP Negeri 2 Kalipuro. Hasil analisis validitas memperoleh presentase sebesar 96,66%, analisis praktikalitas memperoleh presentase sebesar 94%, dan analisis efektivitas memperoleh nilai N-gain sebesar 0,69 yang termasuk dalam kategori sedang dan juga presentase respon siswa sebesar 83,7%. Dari hasil tersebut dapat disimpulkan bahwa e-modul berbasis Moodle dalam pembelajaran IPA dapat dikatakan valid, praktis dan efektif dalam meningkatkan keterampilan argumentasi ilmiah siswa.